Lessons from cross-pathogen studies: understanding the metabolic rewiring of macrophages upon infection - Perez-Toledo, Marisol; Llibre, Alba (Frontiers in Cellular and Infection Microbiology, 2025)
Bacterial infections remain a significant cause of morbidity and mortality globally. Compounding the issue is the rise of antimicrobial-resistant strains, which limit treatment options. Macrophages play key roles in the immunity and pathogenicity of intracellular infections, such as those caused by Mycobacterium tuberculosis and Salmonella. Recent advancements have enabled us to better understand how the host orchestrates immune responses to fight these infections and, specifically how the infected cell rewires its metabolism to face this challenge. The engagement of the host cell in specific metabolic pathways impacts cell function and behaviour, and ultimately, infection outcomes. In this perspective, we summarise key findings regarding the metabolic adaptations in macrophages induced by Mycobacterium tuberculosis and Salmonella infections. We also explore how cross-pathogen studies can deepen our insights into infection biology to improve therapeutic design.